Kesesuaian Pelayanan Informasi Obat (PIO) di Apotek Kecamatan Tulung Kabupaten Klaten - Rahmi Nurhaini; Fany Munasari; Ratna Agustiningrum (Universitas Muhammadiyah Klaten, 2020)
Drug Information Services (PIO) at this time is not just delivering drugs but drugs must be clearly informed to patients so that patients are not mistaken in using the drugs received. A service is considered good if it is in accordance with established standards. This study aims to determine the suitability of information services carried out by Pharmacists in Apotek Kecamatan Tulung Kabupaten Klaten. This research is descriptive in nature using total sampling. The sample in this study were 3 Pharmacists. The results showed that the suitability of drug information service (PIO) in Apotek Kecamatan Tulung Kabupaten Klaten was the most frequently performed namely explaining the time of use of the drug 100% always done and explaining the amount of drug taken at the time drinking in patient 100% always done while explaining the side effects medication from drugs given to patients 100% rerely done.